A Response to Guy - Lawrence, Constance (Journal of psychology and theology, 1987)
A brief response is made to the concerns raised by James Guy (1987) in his reaction to “An Integrated Spiritual and Psychological Growth Model in the Treatment of Narcissism” (Lawrence, 1987).